The rationale behind the concept of goal. Issue 3 (31st March 2016) - GOVERNATORI, GUIDO; OLIVIERI, FRANCESCO; SCANNAPIECO, SIMONE; ROTOLO, ANTONINO; CRISTANI, MATTEO
Abstract: The paper proposes a fresh look at the concept of goal and advances that motivational attitudes like desire, goal and intention are just facets of the broader notion of (acceptable) outcome. We propose to encode the preferences of an agent as sequences of "alternative acceptable outcomes". We then study how the agent's beliefs and norms can be used to filter the mental attitudes out of the sequences of alternative acceptable outcomes. Finally, we formalise such intuitions in a novel Modal Defeasible Logic and we prove that the resulting formalisation is computationally feasible.